Intermitências da imagem: um diálogo com o tempo - Rodrigo Freitas Rodrigues (2016)
Disappearances and survivals, apparitions and fascination give the image its own temporality, which is a present kept in suspension and constituted of multiple pasts. Additionally, the displacement of images through many media destabilizes the chronological linearity by making apparent the temporal density that constitutes image itself. In order to approach these issues, we began with considerations of Maurice Blanchot and Didi-Huberman, whose reading of Warburg and Benjamin, contributes to the understanding of image as a historical agent, through which the past appears unexpectedly in the present as a survivor gesture, a flash. During the research we observe other authors and artists, particularly the work of Tacita Dean, which was chosen by its decisive relevance to the proposed theme and which whom I share some interests, although I my work differs from it in terms of procedures and means. The thoughts developed throughout this study about the relationship between image and time first appeared in my own artistic practice, in which the painting is crossed by references from photography, cinema, surveillance cameras and, more recently, drones, sonars and infrared cameras. The aim, therefore, is a navigation in this sea, which is the image itself.